ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS LABA STUDI KASUS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI - Duma Rachel Situmorang (LP2MTBM MAKARIOZ, 2018)
Earnings information which owned by the manufacturing company will be beneficial for theusers of financial statements.The purpose of this study is to analyze and provide empirical evidence of size, liquidity, leverage, and investment opportunity set that affect the quality of corporate profits partially and simultan.Populasi in this study as many as 7 companies, After going through the stage of purposive sampling, the sample used as many as 4 companies listed on the Indonesia Stock Exchange, for the period 2009-2016.. This research stated that the independent variables namely size, liquidity, laverage, and investment opportunity set simultaneously have a significant positive effect on the dependent variable that is profit quality. Partially independent variable that is liquidity and IOS which have positive significant effect to dependent variable that is profit quality.